Importance of Intermolecular Hydrogen Bonding for the Stereochemical Control of Allene–Enone (3+2) Annulations Catalyzed by a Bifunctional, Amino Acid Derived Phosphine Catalyst. (6th January 2016) - Holland, Mareike C.; Gilmour, Ryan; Houk, K. N.
Abstract: The origin of stereoselectivity in the (3+2) annulation of allenes and enones catalyzed by an amino acid derived phosphine catalyst has been investigated by the use of dispersion‐corrected density functional theory. An intermolecular hydrogen bond between the intermediate zwitterion and the enone was found to be the key interaction in the two enantiomeric transition states. Additional stabilization is provided by intermolecular hydrogen‐bonding interactions between acidic positions on the catalyst backbone and the substrate. Enantioselectivity occurs because the intermolecular hydrogen bond in the transition state leading to the minor enantiomer is only possible at the expense of reactant distortion.